If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3=s+68/8
We move all terms to the left:
3-(s+68/8)=0
We add all the numbers together, and all the variables
-(+s+68/8)+3=0
We get rid of parentheses
-s+3-68/8=0
We multiply all the terms by the denominator
-s*8-68+3*8=0
We add all the numbers together, and all the variables
-s*8-44=0
Wy multiply elements
-8s-44=0
We move all terms containing s to the left, all other terms to the right
-8s=44
s=44/-8
s=-5+1/2
| -4.5(x-5)=13.5 | | 11z+44=37z-34 | | x-41.5=57 | | 2x+15=42-x | | 54=-9m | | 45c-50=20c | | 6x+24=14x | | -9q-6=-11q | | 2p+19=3p-12 | | b+28=49 | | 14a=6a+16 | | -322=-7(6+5k) | | 5d=-95 | | 14a-2=16a-14 | | 5x-(x-2)=50 | | 9q-3=-3-3q | | y2-3y+2y-6=y2+9y-6y-54+8 | | 7t-15=2t+20 | | 3=-y/4 | | -s/3=2 | | v=3*4*6 | | 15u=64+7u | | -6z=7-7z | | t+-1=12 | | 6a+18=17a+14 | | v/7+35=42 | | 45-3w=2w | | 4+r=19 | | s-10=20.19+5.73 | | w+20/11=3 | | 7+5b=-5+10+3b | | 2p=3p-14 |